PERLINDUNGAN KONSUMEN ATAS PENARIKAN PAKSA OLEH DEBT COLLECTOR PERSPEKTIF SIYASAH MALIYAH (Studi Kasus di Badan Penyelesaian Sengketa Konsumen Kota Tasikmalaya) - Munir, Asep; A. Arsyul Munir, Asep (Siyasyatuna | Jurnal Hukum Tata Negara, 2023)
Consumer Protection of Forced Withdrawal by Debt Collectors in the Perspective of Siyasah Maliyah (Case Study at the Tasikmalaya City Consumer Dispute Resolution Agency). In this writing using empirical legal research methods or commonly called sociological juridical research. Data collection techniques by means of observation and interviews. The purpose of this research is one of them: 1) To find out the objective conditions of forced withdrawal carried out by the Debt Collector. 2) To find out the role of the Consumer Dispute Resolution Body against consumers for forced withdrawal by Debt Collectors in terms of Law No. 8 of 1999 concerning consumer protection. 3) To find out the sanctions for Debt Collectors who make forced withdrawals against victims / debtors. The results of this study can be concluded that the forced withdrawal of vehicles carried out by Debt Collectors against consumers violates the current legal rules, and can even be punished with multiple articles